2007
DOI: 10.1590/s1415-52732007000100001
|View full text |Cite
|
Sign up to set email alerts
|

Panorama das ações de controle da deficiência de vitamina A no Brasil

Abstract: Este trabalho propõe-se a descrever a trajetória da implantação das ações de controle da deficiência de vitamina A no Brasil. MétodosTrata-se de estudo baseado em dados secundários, obtidos nos registros, documentos técnicos e relatórios oficiais do Instituto Nacional de Alimentação e Nutrição, autarquia do Ministério da Saúde extinta em 1997, da Coordenação Geral da Política Nacional de Alimentação e Nutrição do Ministério da Saúde, e informações obtidas com informantes-chaves, empregando a abordagem multidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
23

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 10 publications
1
15
1
23
Order By: Relevance
“…The state of Paraiba was a pioneer in establishing this program in the 1980s. According to Martins et al (2007), this state showed the highest levels of coverage and regularity between 1996 and 1998, compared to other states included in the Program. 10 Bearing in mind the high prevalence of Vitamin A defi ciency in Paraiba found in the 1992 survey and the lack of subsequent studies evaluating trends in this defi ciency, the aim of this study was to analyze the prevalence of VAD in children and associated factors.…”
mentioning
confidence: 91%
“…The state of Paraiba was a pioneer in establishing this program in the 1980s. According to Martins et al (2007), this state showed the highest levels of coverage and regularity between 1996 and 1998, compared to other states included in the Program. 10 Bearing in mind the high prevalence of Vitamin A defi ciency in Paraiba found in the 1992 survey and the lack of subsequent studies evaluating trends in this defi ciency, the aim of this study was to analyze the prevalence of VAD in children and associated factors.…”
mentioning
confidence: 91%
“…6,28 Thus, in ideal breastfeeding conditions, breast milk is considered the most important source of VA to multiply the infant's hepatic reserves and the great protective factor against Vitamin A deficiency (VAD) until two years of age, the peak of vulnerability. 29 However, certain maternal factors may influence retinol concentrations in breast milk, among them the lactation stage; 30 breastfeeding process; 31 gestational age; 32 ; parity 33 ; VA in maternal diet; 34 zinc's nutritional state; 22 and pathologies as diabetes mellitus. [35][36][37][38][39] Vitamin A: rbP and diabetes mellitus Individuals with diabetes mellitus have been considered a group in risk of presenting marginal nutritional state or deficient in many related micronutrients and composites, such as vitamins A, E, C and carotenoids.…”
Section: Vitamin A: Metabolism and Functionsmentioning
confidence: 99%
“…O programa é executado nas secretarias estaduais e municipais de saúde, bem como nas coordenações estaduais de alimentação e nutrição, com o apoio do Fundo das Nações Unidas para a Infân-cia (UNICEF) e da Organização Pan-Americana de Saúde (OPAS) 17 .…”
Section: Histórico Das Ações De Educação Nutricional No Controle Da Dunclassified
“…A estratégia de distribuição de megadoses de vitamina A, integrada ao Programa Nacional de Imunização, tornou o Brasil pioneiro nessa iniciativa, que passou a ser posteriormente preconizada pela Organização Mundial de Saúde em vários países, como medida eficiente de combate da DVA 17 . Por outro lado, uma avaliação recente do atual Programa Nacional de Suplementação de Vitamina A ("Vitamina A Mais") realizada no estado da Bahia, no período de 1999 a 2002 21 mostrou que a realização de atividades educativas, previstas a longo prazo, e que deveriam ser executadas pelos gestores locais, visando ao aumento do consumo de alimentos ricos em vitamina A, não aconteceu e/ou não produziu os resultados esperados.…”
Section: Histórico Das Ações De Educação Nutricional No Controle Da Dunclassified